The poetics of empowerment in David Mitchell's novels - Windberger, Eva-Maria (New York, NY : Routledge, 2023)
"The Poetics of Empowerment in David Mitchell's Novels combines the investigation of David Mitchell's novels with the introduction of a new critical concept to literary studies: empowerment. Aiming to situate and establish empowerment firmly within the context of literary studies, it offers the first framework and definition for reading fictional texts with the lens of empowerment and applies it in the analysis of discourse, the fictional characters, and the role of the reader in Mitchell's novels. Drawing on narratological analysis, cognitive approaches to literature, and reader-response theory, it features close readings of Cloud Atlas (2004), Black Swan Green (2006), and The Thousand Autumns of Jacob de Zoet (2010) and dissects the author's strategies, poetics, and agenda of empowering fiction. This book argues for an inherent, indissoluble connection between empowerment and the telling of stories and demonstrates how literary studies can benefit from a serious engagement with empowerment-and how such an engagement can stimulate new responses to fiction and put literary studies in conversation with other disciplines"--
Keywords: Mitchell, David -- Criticism and interpretation; Power (Social sciences) in literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; POLITICAL SCIENCE / Political Freedom & Security / General